PELATIHAN MANAJEMEN STRES PADA IBU HAMIL DI PUSKESMAS BOJONG MENTENG KOTA BEKASI - Tati Nuryati; Handayani (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Pregnancy stress is one of the phenomena experienced by every mother, especially mothers who experience pregnancy for the first time (primigravida) which is triggered by a bad event that will happen to them. Psychological factors that occur in pregnant women are influenced by various things, namely the presence of both internal and external stress, family support, substance abuse and partner abuse. (Jatnika et al., 2016). Results Based on research that the proposer has done at the Bojong Menteng Health Center and several studies prove that pregnant women experience stress during many pregnancies. This stress has a negative impact on the unborn baby and also has a negative impact on pregnant women. The impact of stress can be in the form of heart palpitations, increased blood pressure, increased stomach acid, heavy breathing and shortness of breath, emotional changes that can even cause early contractions during pregnancy, hyperemesis gravidarum, abortion, and eclampsia which are very life-threatening for pregnant women and can even cause death. Thus the LPPM UHAMKA Partner Cooperation Program (PKM) in community service offers solutions, including stress management and relaxation training for pregnant women through the Pregnant Women Class at the Bojong Menteng Health Center. stress during pregnancy. The method is coordinated with the Head of the Bojong Menteng Health Center, early detection of mental health of pregnant women through interviews, and counseling "Stress Management in Pregnant Women with interactive lecture methods, question and answer, brainstorming and relaxation practices to overcome stress. After completing learning, learning evaluation is carried out, and recording reports The results of early detection of 45 pregnant women found 14 pregnant women (31.1%). pregnant